BIM in principle and in practice - Barnes, Peter, 1954-; Davies, Nigel (ICE Publishing, 2014)
Covering the principles behind building information modelling (BIM), its current use in practice and how it may develop in the future, 'BIM in Principle and in Practice' provides construction professionals with an overview of this emerging field to enable informed discussions with clients and colleagues.